Water Tree Mapping in Submarine High Voltage Cables Using Finite Element Method - Ryeskog, Carl-Adam; Novljanin, Hazim (My University, 2025)
Abstract Water treeing is a degradation phenomenon that occurs in submarine power cables. It is one of the main causes of failures of dynamic cables attached to mobile floating platforms. The rough sea environment causes mechanical stresses in the insulation of dynamic cables provoking appearance of microscopic cracks and water intrusion. The combination of water and enhanced electric fields can cause electrical, chemical, and mechanical reactions to occur which intensify water tree growth in cable insulation. This thesis aims to contribute to the development of a numerical model for simulating water treeing in high voltage insulating materials. The scope of the thesis is limited to the electrical aspects of the water treeing. COMSOL Multiphysics is used to model the conditions for experimental water tree testing according to ASTM D6097 standard. The model considers the current flow in the polymeric insulation due to the applied electric stress and so-called state variable is used to map healthy and damaged regions in the insulation material. The latter is identified as a domain where the electric field exceeds the threshold corresponding to initiation of defects in the polymer due to appearing internal electrostatic forces. Validation is done by comparing the simulation to the standard and experiments reported in the literature. The results show that the numerical model follows previous observations and may be used as a base for further development of the tools for predicting insulation lifetime.
Keywords: Keywords: water treeing, FEM, COMSOL, subsea cables, dynamic cables